Electron Doping a Kagome Spin Liquid - Z. A. Kelly; M. J. Gallagher; T. M. McQueen (Physical Review X, 2016)
Herbertsmithite, ZnCu_{3}(OH)_{6}Cl_{2}, is a two-dimensional kagome lattice realization of a spin liquid, with evidence for fractionalized excitations and a gapped ground state. Such a quantum spin liquid has been proposed to underlie high-temperature superconductivity and is predicted to produce a wealth of new states, including a Dirac metal at 1/3 electron doping. Here, we report the topochemical synthesis of electron-doped ZnLi_{x}Cu_{3}(OH)_{6}Cl_{2} from x=0 to x=1.8 (3/5 per Cu^{2+}). Contrary to expectations, no metallicity or superconductivity is induced. Instead, we find a systematic suppression of magnetic behavior across the phase diagram. Our results demonstrate that significant theoretical work is needed to understand and predict the role of doping in magnetically frustrated narrow band insulators, particularly the interplay between local structural disorder and tendency toward electron localization, and pave the way for future studies of doped spin liquids.